2021
DOI: 10.3390/ejihpe11020043
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Body Dissatisfaction and Eating Disorder Symptoms in Young Women Aspiring Fashion Models: The Mediating Role of Stress

Abstract: It is widely recognized that body dissatisfaction is an important public health concern. In the past, being a fashion model was almost synonymous with anorexia/bulimia, and even today, there are cases of eating disorders in young women whose ambition is to become a top model. Moreover, stress can play a substantial role within ill health via related behaviors such as smoking, substance abuse, and inappropriate eating. In our study, we examined 112 aspiring fashion models aged between 15 and 24 years (M = 19.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…This over-representation in the clinical subsample could be justified by a higher pressure over the body due to the higher body exposition given by the participation in advertising campaigns. At the same time, the use of body edition techniques is common in the advertising field, which increases body dissatisfaction and the wish for the body shape shown in the images (49,(63)(64)(65). Body dissatisfaction could be higher when the economic interests of the sports club are linked to the advertising activities because this could imply a higher pressure on the selfbody and an increase in perceived stress (18).…”
Section: Influence Of the Different Variables On Eating Disorders Ris...mentioning
confidence: 99%
“…This over-representation in the clinical subsample could be justified by a higher pressure over the body due to the higher body exposition given by the participation in advertising campaigns. At the same time, the use of body edition techniques is common in the advertising field, which increases body dissatisfaction and the wish for the body shape shown in the images (49,(63)(64)(65). Body dissatisfaction could be higher when the economic interests of the sports club are linked to the advertising activities because this could imply a higher pressure on the selfbody and an increase in perceived stress (18).…”
Section: Influence Of the Different Variables On Eating Disorders Ris...mentioning
confidence: 99%
“…3. Other authors [4] picked out similar behaviors associated with inappropriate eating among women, although the prevalence was lower: snacking during the day ( ̅ = 2.17; SD = 1.07), eating too little in the first half of the day and then too much in the second half of the day ( ̅ = 2.07; SD = 1.21), eating while doing other activities ( ̅ = 2.04; SD = 1.22). The results of both studies indicate that the girls' eating regularity is improper.…”
Section: Girls' Improper Eating Behaviormentioning
confidence: 99%
“…Health behaviors refer mainly to cognitive, behavioral and emotional components. They combine emotions, beliefs, and tendencies to behave positively or negatively, therefore their nature is very complex [4,5,12]. Health behavior is an integral component of the socialization process, which responds to the influence of different environments: family, school, peers, mass media and social media [16,25].…”
Section: Introductionmentioning
confidence: 99%
“…Aspects such as feeling bloated after eating a normal amount of food are common features among people who feel dissatisfied with their own bodies [ 11 , 27 , 28 ]. Given that body dissatisfaction is endemic among young women in Western cultures it cannot be concluded that this construct alone causes EDs.…”
Section: Introductionmentioning
confidence: 99%
“…Given that body dissatisfaction is endemic among young women in Western cultures it cannot be concluded that this construct alone causes EDs. However, it is a risk factor responsible for the initiation and maintenance of extreme weight control behaviors that lead to the development of EDs in those who are vulnerable [ 5 , 11 , 28 ].…”
Section: Introductionmentioning
confidence: 99%